Interpopulation variation in seed traits of five Polygonaceae - Bhatt, Arvind; Phartyal, Shyam S.; Daibes, L. Felipe; Chen, Xingxing (Frontiers in Ecology and Evolution, 2023)
Interpopulation variability in seed traits may drive the regeneration capacity of a species to colonize different environments. In the present study, we evaluated variation in seed physical (mass/size, water imbibition, shape index) and physiological (germination) traits of five Polygonaceae species. Seeds of Polygonum lapathifolium var. salicifolium, P. lapathifolium, Reynoutria japonica, Rumex trisetifer, and R. obtusifolius were collected from two or three populations in Jiujiang, China. Physical seed traits were measured before germination tests under different combinations of light and temperatures. Most species had a significant variation in seed traits, although populations are geographically close. Interpopulation variation in seed traits appeared to be species-specific, with the highest variation for R. japonica and lowest for R. trisetifer seeds. Germination response to temperature and light conditions also varied among species and populations, being mostly inhibited in the dark treatments. Light dependency of germination can be related to the small seed size, except for the round-seeded Rumex, depending on the temperature regime. Optimal temperature ranges mainly varied from 10/20°C to 25/35°C, with significant decreases in germination percentage at both coolest and warmest extremes. Germination requirements seem to be related to altitudinal gradients in populations of P. lapathifolium and R. japonica seeds.